A Contextual Analysis of Human Resource Development for Promoting Public Welfare in the Digital Transformation Era: The Case of Nabire Regency - Napan, Carles; Baharuddin; Lambe, Kristian Hoegh Pride (Journal of Marketing Management and Innovative Business Review, 2025)
This study aims to examine the contextual development of human resources (HR) in supporting public welfare during the era of digital transformation in Nabire Regency. Employing a qualitative-descriptive approach, data were collected through in-depth interviews, field observations, and document analysis involving stakeholders from government, education, and public communication sectors. The findings reveal that despite growing awareness of digitalization, key challenges persist, including limited digital literacy, inadequate technological infrastructure, and disparities in HR competencies. Contextual strategies—such as mobile training units, community-based outreach, and engagement of local leaders—have proven effective in reaching remote areas. The study underscores the need for inclusive policies and cross-sectoral collaboration to build a sustainable HR development ecosystem responsive to technological change. The research concludes that digital transformation can serve as a catalyst for public welfare if supported by competent and locally attuned human resources.